2012
DOI: 10.5402/2012/729086
|View full text |Cite
|
Sign up to set email alerts
|

Hemostatic Agents in Hepatobiliary and Pancreas Surgery: A Review of the Literature and Critical Evaluation of a Novel Carrier-Bound Fibrin Sealant (TachoSil)

Abstract: Background. Despite progress in surgical techniques applied during hepatobiliary and pancreas (HPB) surgery, bleeding and bile leak remain significant contributors to postoperative mortality and morbidity. Topical hemostatics have been developed and utilized across surgical specialties, but data regarding effectiveness remains inconsistent and sparse in HPB surgery. Methods. A comprehensive search for studies and reviews on hemostatics in HPB surgery was performed via an October 2011 query of Medline, EMBASE, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 54 publications
1
28
0
1
Order By: Relevance
“…A recent review of fibrin sealant in hepatic surgery, also supports the findings [217] that fibrin sealant may be an effective hemostat but thus far does not seem to reduce complications. One multicenter, prospective, randomized study [214] suggested that a patch composed of polyethylene glycol, trilysine amine, and oxidized regenerated cellulose ( n = 32) was superior to a fibrin sealant-equine collagen patch ( n = 18) in terms of median time to hemostasis (1.0 versus 3.0 min, P < 0.001) during hepatic resection.…”
Section: Less Frequently Published Clinical Applications Of Fibrinmentioning
confidence: 67%
“…A recent review of fibrin sealant in hepatic surgery, also supports the findings [217] that fibrin sealant may be an effective hemostat but thus far does not seem to reduce complications. One multicenter, prospective, randomized study [214] suggested that a patch composed of polyethylene glycol, trilysine amine, and oxidized regenerated cellulose ( n = 32) was superior to a fibrin sealant-equine collagen patch ( n = 18) in terms of median time to hemostasis (1.0 versus 3.0 min, P < 0.001) during hepatic resection.…”
Section: Less Frequently Published Clinical Applications Of Fibrinmentioning
confidence: 67%
“…ORC conducts hemostatic action through blood absorption, surface interaction with platelets (PLTs) and proteins, and coagulation cascade activation 11. Since its introduction in 1943, several commercial ORC products have been developed,12 and are now frequently used in most gastrointestinal and non-gastrointestinal operations 1314…”
Section: Introductionmentioning
confidence: 99%
“…Время остановки кровотечения определяют по прекращению истечения крови после очередного снятия местного гемоста-тика [39] (губки, пленчатого импланта и др.) с поверхности раны.…”
Section: методы исследования гемостатической активности аппликационныunclassified